To Wait or Not to Wait: Swiss EU-Membership as an Investment under Uncertainty - Beat Spirig; Rolf Weder (Swiss Journal of Economics and Statistics, 2008)
Why do some countries join the EU earlier than others, why do others wait? In order to answer this question we apply the theory of investment under uncertainty (Dixit and Pindyck, 1994) to the decision on EU-membership. We develop a simplified model of two periods to study how the value of waiting depends among other things on the degree of uncertainty. The results give rise to a country?s position to deliberately postpone a membership in order to keep the option to join later if this is desirable. After interpreting the results we illustrate the framework by applying it to Switzerland and the new EU-members, taking into account the EU?s draft of the Constitutional Treaty. We argue that the approach provides interesting insights regarding EU-membership, in general, and the Swiss position, in particular.
Keywords: D81; F02; 330; European integration; investment under uncertainty; EU-membership